2012
DOI: 10.1523/jneurosci.5088-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Activated Potassium Channels Are Functionally Coupled to Persistent Sodium Currents

Abstract: We report a novel coupled system of sodium-activated potassium currents (IKNa) and persistent sodium currents (INaP), the components of which are widely distributed throughout the brain. Its existence and importance has not been previously recognized. Although IKNa was known to exist in many cell types, the source of Na+ which activates IKNa remained a mystery. We now show in single membrane patches generated from the somas of rat neurons that sodium influx through INaP is sufficient for activation of KNa chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
116
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(132 citation statements)
references
References 31 publications
15
116
1
Order By: Relevance
“…Thus we conclude that both TTXand Cd 2ϩ -sensitive I NaP may participate largely in elevating intracellular Na ϩ concentration ([Na ϩ ] i ) and accordingly activate K Na channels. These results are consistent with previous studies demonstrating that TTX-sensitive I NaP are the source of Na ϩ for the activation of K Na channels in tufted/mitral cells of the olfactory bulbs (Budelli et al 2009;Hage and Salkoff 2012).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus we conclude that both TTXand Cd 2ϩ -sensitive I NaP may participate largely in elevating intracellular Na ϩ concentration ([Na ϩ ] i ) and accordingly activate K Na channels. These results are consistent with previous studies demonstrating that TTX-sensitive I NaP are the source of Na ϩ for the activation of K Na channels in tufted/mitral cells of the olfactory bulbs (Budelli et al 2009;Hage and Salkoff 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Subsequently, considerable evidence has accumulated showing that K Na channels play a role in the regulation of neuronal excitability (Schwindt et al 1989), the modulation of action potential waveform (Dryer 1994), and the response of excitable cells to hypoxia and ischemia (Yuan et al 2003). Recently, it was shown that K Na channels are activated by Na ϩ influx through TTX-sensitive persistent Na ϩ channels in tufted/mitral cells of the olfactory bulb (Hage and Salkoff 2012), thus showing functional coupling between Na ϩ -activated K ϩ channels and TTX-sensitive persistent Na ϩ currents. K Na channels are found in insect neurons such as cockroach DUM neurons (Grolleau and Lapied 1994) and in cultured Drosophila neurons (Saito and Wu 1991).…”
mentioning
confidence: 99%
“…TTX, however, also completely eliminates K Na currents that are functionally coupled to the I NaP channels (Hage and Salkoff, 2012). The observed increase in I NaP in the animal models of ALS may therefore represent loss of K Na current rather than, or in addition to, increased Na ϩ current.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have pointed to an increase in a persistent voltage-dependent Na ϩ current as a cause of increased excitability, although changes in outward currents have also been reported (Kuo et al, 2005;Wainger et al, 2014). In neurons, however, the persistent Na ϩ current rapidly and selectively activates Na ϩ -activated K ϩ channels (K Na channels) (Hage and Salkoff, 2012). These are encoded by the Slack (K Na 1.1, Slo2.2, KCNT1) and Slick (K Na 1.2, Slo2.1, KCNT2) genes .…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation